Collagen VI Null Mice as a Model for Early Onset Muscle Decline in Aging - Capitanio, Daniele; Moriggi, Manuela; De Palma, Sara; Bizzotto, Dario; Molon, Sibilla; Torretta, Enrica; Fania, Chiara; Bonaldo, Paolo; Gelfi, Cecilia; Braghetta, Paola (Frontiers in Molecular Neuroscience, 2017)
Collagen VI is an extracellular matrix (ECM) protein playing a key role in skeletal muscles and whose deficiency leads to connective tissue diseases in humans and in animal models. However, most studies have been focused on skeletal muscle features. We performed an extensive proteomic profiling in two skeletal muscles (diaphragm and gastrocnemius) of wild-type and collagen VI null (Col6a1−/−) mice at different ages, from 6- (adult) to 12- (aged) month-old to 24 (old) month-old. While in wild-type animals the number of proteins and the level of modification occurring during aging were comparable in the two analyzed muscles, Col6a1−/− mice displayed a number of muscle-type specific variations. In particular, gastrocnemius displayed a limited number of dysregulated proteins in adult mice, while in aged muscles the modifications were more pronounced in terms of number and level. In diaphragm, the differences displayed by 6-month-old Col6a1−/− mice were more pronounced compared to wild-type mice and persisted at 12 months of age. In adult Col6a1−/− mice, the major variations were found in the enzymes belonging to the glycolytic pathway and the tricarboxylic acid (TCA) cycle, as well as in autophagy-related proteins. When compared to wild-type animals Col6a1−/− mice displayed a general metabolic rewiring which was particularly prominent the diaphragm at 6 months of age. Comparison of the proteomic features and the molecular analysis of metabolic and autophagic pathways in adult and aged Col6a1−/− diaphragm indicated that the effects of aging, culminating in lipotoxicity and autophagic impairment, were already present at 6 months of age. Conversely, the effects of aging in Col6a1−/− gastrocnemius were similar but delayed becoming apparent at 12 months of age. A similar metabolic rewiring and autophagic impairment was found in the diaphragm of 24-month-old wild-type mice, confirming that fatty acid synthase (FASN) increment and decreased microtubule-associated proteins 1A/1B light chain 3B (LC3B) lipidation are hallmarks of the aging process. Altogether these data indicate that the diaphragm of Col6a1−/− animal model can be considered as a model of early skeletal muscle aging.